Rehabilitación estructural de un sector afectado por corrosión severa en vigas de entrepiso en una curtiembre - PeirénCascino, Soledad (Revista ALCONPAT, 2011)
The fall of part of a beam located at 6m of height led to a diagnosis and rehabilitation projectwithin an area of an industrial plant in Paysandú, Uruguay.The aim of this work is to show a case study that would allow avoiding future risky inefficient repairs. A visual inspection and an analysis of the background of the problem revealed that a previous intervention had taken place, which favored the corrosion of the reinforcement and internal cracking of the structural elements; such factors caused partial spalling of the concrete. The causes of the pathologies described in this report were originated by inadequate coating of the reinforcement as well as the corrosive industrial environment.Key words: rehabilitation; pathology; corrosión; structure.